2016
DOI: 10.1093/rheumatology/kew463
|View full text |Cite
|
Sign up to set email alerts
|

URAT1 inhibition by ALPK1 is associated with uric acid homeostasis

Abstract: Elevated ALPK1 expression decreased URAT1 expression. ALPK1 might prevent the impact of urate reuptake via SLC22A12 and appeared to be negatively associated with gout. ALPK1 is a potential repressor of URAT1 protein expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The rs7442295 single nucleotide polymorphism or loss-of-function mutation in the solute carrier family (SLC) 2, facilitated glucose transporter member 9 (SLC2A9) gene encoding for GLUT9 which results in reduced secretion of urate into urine and increased absorption into the bloodstream [39,40]. A similar pattern of hyperuricemia has been reported in the rs475688, rs3825016, and rs11726117 polymorphisms of the SLC22A12 gene encoding for URAT1 which results in renal hypouricemia type 1 [41,42]. A similar outcome has been observed with the rs2231142 single nucleotide polymorphism of the BCRP gene encoding for ABCG2 in addition to defective intestinal urate excretion [43,44].…”
Section: Ua and Genetic Variationsmentioning
confidence: 90%
“…The rs7442295 single nucleotide polymorphism or loss-of-function mutation in the solute carrier family (SLC) 2, facilitated glucose transporter member 9 (SLC2A9) gene encoding for GLUT9 which results in reduced secretion of urate into urine and increased absorption into the bloodstream [39,40]. A similar pattern of hyperuricemia has been reported in the rs475688, rs3825016, and rs11726117 polymorphisms of the SLC22A12 gene encoding for URAT1 which results in renal hypouricemia type 1 [41,42]. A similar outcome has been observed with the rs2231142 single nucleotide polymorphism of the BCRP gene encoding for ABCG2 in addition to defective intestinal urate excretion [43,44].…”
Section: Ua and Genetic Variationsmentioning
confidence: 90%
“…33 We have demonstrated abundant expression of ALPK1 in renal tubular cells of mice. 6 These shreds of evidence strongly suggest that ALPK1 enhances CCL2 and CCL5 expression through NFkB activation in hyperglycaemic conditions in renal tubular cells.…”
Section: Discussionmentioning
confidence: 95%
“…The variant p. (T237M) could represent an extreme phenotype of the same spectrum, where NLRP3 inflammasome activation mediated by an overactive ALPK1 kinase could trigger all the phenotypic aspects described in carriers of this variant. ALPK1 has never been implicated before in the periodic fever syndromes, but its role in the innate immunity is well established and previous genomic studies found an association, in some populations, between specific ALPK1 variants with gout [23,29,30], that is considered a polygenic autoinflammatory disease. Future analyses on additional patients, even with an extended autoinflammatory phenotypic spectrum and functional tests on mutated ALPK1 proteins, will help to identify a precise role for this gene in the recurrent fever phenotype.…”
Section: Discussionmentioning
confidence: 99%